Gender, psychology, and justice : the mental health of women and girls in the legal system - Datchi, Corinne C.; Ancis, Julie R. (Psychology and crime series., 2017)
"Women and girls' contact with the justice system is often influenced by gender-related assumptions and stereotypes. The justice practices of the past 40 years have been largely based on conceptual principles and assumptions (including personal theories about gender) more than scientific evidence about what works to address the specific needs of women and girls in the justice system. Because of this, women and girls have limited access to equitable justice and are increasingly caught up in outdated and harmful practices, including the net of the criminal justice system. [This book] uses psychological research to examine the experiences of women and girls involved in the justice system. Their experiences, from initial contact with justice and court officials, demonstrate how gender intersects with race, class, and sexual orientation to impact legal status and well-being. The volume also explains the role psychology can play in shaping legal policy, ranging from the areas of corrections to family court and drug court. [The authors analyze] girls' and women's experiences in the justice system. It reveals the practical implications of training and interventions grounded in psychological research, and suggests new principles for working with women and girls in legal settings."--